How Muslims in the UK Experience Coaching using the Ershad Framework: An Interpretative Phenomenological Analysis - Monia Kamel; Christian van Nieuwerburgh (International Journal of Evidence Based Coaching and Mentoring, 2023)
This study aimed to explore how Muslims in the UK experience coaching using the Ershad framework. The data was derived from four semi-structured interviews that were conducted after a coaching intervention. The study adhered to interpretative phenomenological analysis (IPA) for data analysis. Four themes emerged from the data: “it aligned with our faith”; “I felt comfortable”; “an eye-opening experience”; and connected to deeper self. Findings highlighted that participants valued a culturally sensitive approach, grounded in the principles of effective coaching, and thus support the idea that culturally specific coaching approaches may be beneficial for certain groups of people.